Leaf anatomy and gas exchange of ornamental sunflower in response to silicon application - Luiz Antônio Zanão Júnior; Victor Hugo Alvarez Venegas; Renildes Lúcio Ferreira Fontes; Maristela Pereira Carvalho-Zanão; Jaqueline Dias-Pereira; Leila Teresinha Maranho; Natália Pereira (Bioscience Journal, 2017)
Silicon applied to substrate for greenhouse cultivation of ornamental pot plants can improve the yield and quality of the ornamental product; however, the possible anatomical and physiological changes caused by Si have to be assessed. Therefore, the objective of this study was to evaluate gas exchange rates and leaf anatomy of ornamental sunflower 'Sunbright' grown on a substrate amended with Si. The experiment was conducted in a greenhouse, and the treatments consisted of sunflower plants cultivated in pots containing 600 g substrate fertilized with Si at rates of 0, 0.25, 0.50, 0.75, and 1.00Â g kg-1. The treatments were arranged in randomized complete block design and four replications. Samples from the middle region of leaf blades in the sixth pair from the apex were collected and analyzed morphometrically. Epidermal trichomes were analyzed using diaphanization and scanning electron microscopy with energy-dispersive X-ray spectroscopy. The following traits were determined: leaf blade thickness, palisade and spongy parenchyma thickness, mesophyll thickness, and abaxial and adaxial epidermis thickness. Net photosynthesis, stomatal conductance and transpiration rates were determined in the fifth leaf at the beginning of the flowering stage by an infrared gas analyzer. The data were subjected to ANOVA and regression analyses. The results indicate that the ornamental sunflower 'Sunbright' accumulates Si in leaf trichomes, and that leaf thickness is not affected by Si application to the substrate; however, transpiration rates decrease while net photosynthesis rate and stomatal conductance increase in response to Si application.